A Rapid Prototyping Tool for Embedded, Real-Time Hierarchical Control Systems. (21st December 2008) - Rajagopal, Ram; Ramamoorthy, Subramanian; Wenzel, Lothar; Andrade, Hugo
Abstract : Laboratory Virtual Instrumentation and Engineering Workbench (LabVIEW) is a graphical programming tool based on the dataflow languageG . Recently, runtime support for a hard real-time environment has become available for LabVIEW, which makes it an option for embedded systems prototyping. Due to its characteristics, the environment presents itself as an ideal tool for both the design and implementation of embedded software. In this paper, we study the design and implementation of embedded software by usingG as the specification language and the LabVIEW RT real-time platform. One of the main advantages of this approach is that the environment leads itself to a very smooth transition from design to implementation, allowing for powerful cosimulation strategies (e.g., hardware in the loop, runtime modeling). We characterize the semantics and formal model of computation ofG . We compare it to other models of computation and develop design rules and algorithms to propose sound embedded design in the language. We investigate the specification and mapping of hierarchical control systems in LabVIEW andG . Finally, we describe the development of a state-of-the-art embedded motion control system using LabVIEW as the specification, simulation and implementation tool, using the proposed design principles. The solution is state-of-the-art in terms of flexibility and control performance.